Comprehensive Rehabilitation of Severe Tuberculous Meningitis: A Case Series - Yohan Christian Suisan; Khamim Thohari (Surabaya Physical Medicine and Rehabilitation Journal, 2022)
Tuberculous Meningitis (TBM) is a severely disabling condition that often leads to death. It requires the right intensive treatment to minimize disability, speed up recovery, and reduce the risk of death. Rehabilitation is one of the key components in managing TBM. Rehabilitation is expected to speed up recovery and prevent disabilities. The purpose of this case series was to highlight the effectiveness of a comprehensive rehabilitation program in severe TBM patients at Intensive Care Unit (ICU) settings. We present two cases of severe TBM that showed significant changes after the rehabilitation program started. Both patients were at GCS 111. Rehabilitation program was a therapist-based multimodal sensory stimulation in a comprehensive ICU setting with approximately 2 weeks duration. After 5 days of rehabilitation, the first patient’s consciousness began to improve. The second patient’s consciousness began to improve after 1 week of rehabilitation. After approximately 2 weeks, both of them were already at GCS 456 and then transferred to the High Care Unit (HCU). There were only minor disabilities as they were transferred. The rehabilitation program was adapted and continued at HCU. After 1 month, both of them got discharged to home. These cases highlight the importance of rehabilitation programs to be included in the management of TBM patients.